Why don't we see changes? The role of attentional bottlenecks and limited visual memory - Wolfe, J; Reinecke, A; Brawn, P (2006)
Seven experiments explore the role of bottlenecks in selective attention and access to visual short-term memory (VSTM) in the failure of observers to identify clearly visible changes in otherwise stable visual displays. Experiment 1 shows that observers fail to register a colour change in an object even if they are cued to the location of the object by a transient at that location as the change is occurring. Experiment 2 shows the same for orientation change. In Experiments 3 and 4, attention is directed to specific objects prior to making changes in those objects. Observers have only a very limited memory for the status of recently attended items. Experiment 5 reveals that observers have no ability to detect changes that happen after attention has been directed to an object and before attention returns to that object. In Experiment 6, attention is cued at rates that more closely resemble natural rates and Experiment 7 uses natural images. Memory capacity remains very small (< 4 items). © 2006 Psychology Press Ltd.